Nutrient Element in Soil Cultivation of Neck Orange (Citrus reticulata Lin.) - Mongkol Lim; Charassri Nualsri; Sumalee Suthipradit; Wichai panthanahiran; Suthirak Lim (Agriculture and Natural Resources, 1993)
Cultivation problems of neck oranges decline at Amphur Chana, Songkhla Province, Were investigated. As essential nutrient elements were the first suspected problem, bulk soil samples around the problem site were randomly collected. The soil was mixed, sieved and employed for all glasshouse experiments. There were to find a suitable rate of basal nutrient, to evaluate fertility status of the soil and suitable rates of individual nutrient elements. Maize was used as the tested plant and its shoot dry weight was employed as a measured parameter. Results demonstrated 3xAll of the basal nutrient element gave best growth of maize grown on this soil type. The soil was deficient in N, P, S, Cu, Mo and Zn. Hence, rates of these nutrient elements were studied. It was found that maximum corresponding rates for N, P, S, Cu, Mo and Zn were 120, 150, 75, 6, 0.8 and 5 kg element/ha respectively. There after, these rates of elements were used in a farmer plot to test whether these elements would help in preventing the decline in growth of the neck orange.